HUBUNGAN STATUS PEKERJAAN, INISIASI MENYUSUI DINI, DAN DUKUNGAN SUAMI TERHADAP PEMBERIAN ASI EKSKLUSIF DI PUSKESMAS SUNGAI MENANG TAHUN 2022 - sella sella (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
ABSTRACT Breast milk is the main and most perfect food for babies. Where breast milk contains almost all nutrients with a composition that suits the baby's needs to grow and develop optimall . Data from the World Health Organization (WHO) in 2016 shows that the average exclusive breastfeeding in the world is around 38%. In Indonesia, as many as 96% of women have breastfed their children in their lifetime, but only 42% have received exclusive breastfeedin. The purpose of this study was to determine the relationship between employment status, early initiation of breastfeeding, and husband's support simultaneously with exclusive breastfeeding at the Sungai Menang Health Center, Ogan Komering Ilir Regency in 2022. This study used an analytical survey method with a Cross Sectional approach. This research was carried out by the Sungai Menang Health Center, Ogan Komering Ilir Regency in 2022. With a total sample of 94 respondents, the sampling technique used was the accidental sampling technique. The variables that must be studied are independent (occupational status, early initiation of breastfeeding and husband's support) and dependent (exclusive breastfeeding). The results of the statistical test of the chi-square variable of employment status obtained value = 0.012, early initiation of breastfeeding variable value = 0.005, and husband's support variable value = 0.000 this indicates that there is a significant relationship between employment status, early initiation of breastfeeding and husband's support for exclusive breastfeeding. at Sungai Menang Health Center, Ogan Komering Ilir District in 2022